Training on making processed beef for residents of the Batujajar Transit Apartment, West Bandung Regency - Putri Widyanti Harlina; Arif Nanda Irawan; Rossi Indiarto; Fetriyuna Fetriyuna (Universitas Muhammadiyah Magelang, 2023)
Meat is a nutrient-rich animal food essential for maintaining good health. Given its perishable nature, appropriate processing techniques are crucial to enhance its nutritional value and extend its shelf life. Recognizing the potential of animal-origin food processing and the entrepreneurial opportunities it presents for the community is vital. This community service program aims to educate the community, particularly residents of Batujajar Transit Apartments (Aptrans), on the production of processed meat such as shredded meat, jerky, beef sei, and beef tongue sei. The implementation method of this service includes training, mentoring, and in-depth monitoring to raise awareness about the importance of quality meat as a significant protein source for families. Additionally, it fosters independence and creativity in animal food processing, paving the way for the formation of entrepreneurial partnerships and preparing individuals to initiate businesses. This community service program is executed in collaboration with the Housing and Settlement Service and the West Java Province Housing Management and Services UPTD. The outcomes of this service include heightened creativity and independence in processed meat food preparation, as well as an improved ability to maintain nutritional intake for enhanced nutritional completeness.